2020
DOI: 10.3390/microorganisms8071043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Role of a Non-GPCR Membrane-Bound CFEM Protein in the Pathogenicity and Germination of Botrytis cinerea

Abstract: The necrotrophic fungus Botrytis cinerea, is considered a major cause of postharvest losses in a wide range of crops. The common fungal extracellular membrane protein (CFEM), containing a conserved eight-cysteine pattern, was found exclusively in fungi. Previous studies in phytopathogenic fungi have demonstrated the role of membrane-bound and secreted CFEM-containing proteins in different aspects of fungal virulence. However, non-G protein-coupled receptor (non-GPCR) membrane CFEM proteins have not been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Recent studies have revealed that necrotrophic pathogens also secrete small proteinaceous effectors that can function as pathogenicity factors. Some prominent examples of proteinaceous necrotrophic effectors that induce necrotic cell death include PtrToxA, SnToxA, BcCFEM1, BcXYG1, and the NEP-like proteins in various necrotrophs ( Ciuffetti et al, 2010 ; Dallal Bashi et al, 2010 ; Arya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that necrotrophic pathogens also secrete small proteinaceous effectors that can function as pathogenicity factors. Some prominent examples of proteinaceous necrotrophic effectors that induce necrotic cell death include PtrToxA, SnToxA, BcCFEM1, BcXYG1, and the NEP-like proteins in various necrotrophs ( Ciuffetti et al, 2010 ; Dallal Bashi et al, 2010 ; Arya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In B. Cinerea , the CFEM protein Bcin07g03260 contains only one transmembrane domain, which differs from the G-protein-coupled receptor. When the Bcin07g03260 gene was knockout, the fungus would significantly reduce spore germination and bud tube elongation resulting decreased infection rate on leaves [ 44 ]. In this study, three CFEM proteins from M. anisopliae have multiple transmembrane regions (CFEM82 and CFEM91 with six transmembrane regions, CFEM80 with seven transmembrane regions), and one (CFEM83) has a single transmembrane region ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this gene results in decreased virulence and increased sensitivity to osmotic and cell wall stress, indicating that BcCFEM1 is required for virulence and plays a key role in stress resistance [ 25 ]. The recent work by Arya et al [ 26 ] illustrates a potential new role for a non-GPCR membrane CFEM in pathogenic fungi to control virulence in the fungus B. cinerea .…”
Section: Discussionmentioning
confidence: 99%
“…Target deletion of BcCFEM1 in Botrytis cinerea suggested that the gene contributes to conidial production and stress tolerance, and most importantly the gene disrupt mutants resulted in decreased virulence on French bean ( Phaseolus vulgaris ) leaves, indicated that it was involved in pathogenicity [ 25 ]. Recently, the study by Arya et al indicated that Bcin07g03260 (a non-GPCR membrane-bound CFEM protein) deletion mutants of B. cinerea also showed significantly reduced progression of a necrotic lesion on tomato ( Solanum lycopersicum ) leaves [ 26 ].…”
Section: Introductionmentioning
confidence: 99%